Optimasi Penjadwalan Ujian Tugas Akhir Dengan Menggunakan Algoritma Genetika: Final Project Scheduling Optimization Using Genetic Algorithm - Adi Panca Saputra Iskandar (Journal of Computer Science and Informatics Engineering (J-Cosine), 2021)
Final Project is one of the requirements for STMIK STIKOM Indonesia students to complete their studies. The final project has two stages, namely the proposal seminar process and the final project session, to complete these stages, of course, the study program must make a schedule for the stages. The problem that often occurs in scheduling activities is the occurrence of clashes between one schedule and another, the schedule clashing with the teaching activities of lecturers as supervisors and examiners. and there is a request for lecturer prohibition time to test One method to solve this problem is by using a genetic algorithm that works through natural and genetic selection. There are 8 genetic algorithm procedures, coding technique procedures, initial population and chromosome random (random), fitness function to minimize the number of clashes between schedules, roulette-wheel selection method, crossing over, genetic mutation, elitism and the condition is complete when the maximum iteration has been reached . The output of the system is in the form of lecture scheduling arrangements and final semester exams in PDF file format